?SYNTHESIS OF SOME QUINOXALINE-6-MORPHOLYL SULPHONAMIDE DERIVATIVES - SHARIEF, A.M. SH.EL-; ALl, M M; AMMAR, Y A; SALAM, A A ABDEL- (Biological Sciences - PJSIR, 1996)
Condensation of (III) with amines furnished (IV~.cand Va.b)' while interaction of (III) with sulphanilamide in the presence of anhydrous potassium carbonateyielded (VI).Treatmentof (III)with thiourea caused cyclization and gave (IXa,b and X). Cyclization reaction of (III) with acetonethiosemicarbazone furnished (XI). The reaction of the free base (XII) with carbon disulphide afforded (XVI),which reacted with hydrazine hydrate to give (XVIII). Cyclization of (XVIII) with benzoyl chloride furnished the triazolo-derivative (XIX).